2020
DOI: 10.21873/anticanres.14404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe Infectious Complications on Long-term Prognosis for Gastric Cancer

Abstract: Background: The aim of this study was to evaluate the impact of postoperative infectious complications on longterm outcomes after curative resection of gastric cancer. Patients and Methods: Patients who underwent curative gastrectomy with lymphadenectomy for gastric cancer at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Besides, BMI, pTNM stage and complications were predictive factors for DFS. The results were consisting with previous studies (29,30). Pre-operative lymphocyte was closely associated with human's immune function, and lower level of lymphocyte indicated worse OS in this study (31,32).…”
Section: Cox Regressionsupporting
confidence: 89%
“…Besides, BMI, pTNM stage and complications were predictive factors for DFS. The results were consisting with previous studies (29,30). Pre-operative lymphocyte was closely associated with human's immune function, and lower level of lymphocyte indicated worse OS in this study (31,32).…”
Section: Cox Regressionsupporting
confidence: 89%
“…First, change in the NLR was associated with the occurrence of postoperative complications. Recent studies have shown that the occurrence of postoperative complications affects longterm oncological outcomes in various malignancies [18][19][20]. Therefore, the prognosis might have worsened in patients with an increased NLR due to postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative intraabdominal infection following radical gastrectomy significantly prolongs hospitalization and healthcare costs [ 10 ] and impairs short-term postoperative survival. [ 11 , 12 ] Moreover, the prolonged inflammatory response it induces has a negative impact on recurrence-free survival and overall survival. [ 13 ] Postoperative infection can also promote tumor recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%